2007
DOI: 10.1093/toxsci/kfm063
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Effects of Ammonium Perchlorate on the Hypothalamic-Pituitary-Thyroid Axis of Adult Male Rats Pretreated with PCB126

Abstract: The objective of this research was to characterize the disturbances in the hypothalamic-pituitary-thyroid (HPT) axis resulting from exposure to a binary mixture, 3,3',4,4',5-pentachlorobiphenyl (PCB126) and perchlorate (ClO(4)(-)), known to cause hypothyroidism by different modes of action. Two studies were conducted to determine the HPT axis effects of ClO(4)(-) on adult male Sprague-Dawley rats pretreated with PCB126. In dosing study I, rats were administered a single oral dose of PCB126 (0, 7.5, or 75 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…In reality, endocrine disruptors are rarely present in isolated forms. Interactions among different disruptors are complex and may be additive, sub-additive, and super-additive, depending on the individual combination of substances and their respective concentrations (389–391). This makes the effects difficult to predict in the individual situation.…”
Section: Effects Of Heterogeneous or Unknown Originmentioning
confidence: 99%
“…In reality, endocrine disruptors are rarely present in isolated forms. Interactions among different disruptors are complex and may be additive, sub-additive, and super-additive, depending on the individual combination of substances and their respective concentrations (389–391). This makes the effects difficult to predict in the individual situation.…”
Section: Effects Of Heterogeneous or Unknown Originmentioning
confidence: 99%
“…Iodide ions excreted in urine is the result of metabolic processing of thyroid hormones or due to an excess in plasma concentration after an increase in oral iodine uptake (43). It was reported that about 95% of the daily iodide intake in rats was excreted in urine (11).…”
Section: Discussionmentioning
confidence: 99%
“…We previously simultaneously optimized V max T i (nanomoles per hour) and K NIS TSH (nanomoles per liter) (McLanahan et al 2008) to euthyroid, dietary-iodine–sufficient (~ 20 ÎŒg/day) rat data for serum and thyroid iodide reported by Eng et al (1999) and McLanahan et al (2007), respectively. The other parameter, NIS affinity constant for iodide ( K m i , nanomoles per liter) in Equation 1 was obtained from Gluzman and Niepomniszcze (1983) as reported by McLanahan et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…We obtained physiologic parameters (Table 1) for tissue volumes and blood flows from previous studies (Brown et al 1997; Everett et al 1956; Malendowicz and Bednarek 1986; McLanahan et al 2007, 2008). The BBDR–HPT axis model parameters had been calibrated for the euthyroid adult rat previously and used to describe iodide-deficient conditions (McLanahan et al 2008).…”
Section: Methodsmentioning
confidence: 99%